The Challenges faced by Students in Learning English (Post-Pandemic Era) - Geminastiti Sakkir; Novayanti Sopia Rukmana; Ahmad Bukhori Muslim; Martin Andrew; Maemuna Muhayyang (Universitas Negeri Makassar, 2023)
Abstract. This article was used to describe the challenges that students face when studying English in the new normal era. The qualitative descriptive design was used as the research methodology. The subjects that will be involved are students in SMA/ MA/ SMK/ equivalent in South Sulawesi Province. The data was obtained from the questionnaire Qualitative data analysis techniques were used to analyze the qualitative data. The analysis's results will be presented as a description of the challenges experienced when studying English during the New Normal era. For students, teachers, policymakers, and scholars of education and foreign language learning, this definition will be helpful. This research is related to the implementation of students' English learning strategies in the new normal era. The researcher distributed the questionnaire on the Google Form link to several high school students in South Sulawesi and 206 students sent back the results. The results of the research showed that many challenges faced by students in learning English during the current New Normal (during and after the Covid-19 Pandemic). These challenges come from student conditions, teacher conditions, school conditions, environmental conditions, material conditions, learning processes, and the application of technology. Keywords: Challenges, English, Learning, Strategy.